2022
DOI: 10.3389/fneur.2022.982147
|View full text |Cite
|
Sign up to set email alerts
|

Detecting vulnerable carotid plaque and its component characteristics: Progress in related imaging techniques

Abstract: Carotid atherosclerotic plaque rupture and thrombosis are independent risk factors for acute ischemic cerebrovascular disease. Timely identification of vulnerable plaque can help prevent stroke and provide evidence for clinical treatment. Advanced invasive and non-invasive imaging modalities such as computed tomography, magnetic resonance imaging, intravascular ultrasound, optical coherence tomography, and near-infrared spectroscopy can be employed to image and classify carotid atherosclerotic plaques to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 83 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…Further, previous studies have shown that CTA can identify plaque development following statin therapy ( 35 ). However, due to inadequate imaging resolution, studies have shown that CTA is not very accurate in differentiating between lipids, components of fibrotic tissue, and intraplaque inflammation ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, previous studies have shown that CTA can identify plaque development following statin therapy ( 35 ). However, due to inadequate imaging resolution, studies have shown that CTA is not very accurate in differentiating between lipids, components of fibrotic tissue, and intraplaque inflammation ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that a hybrid approach with IVUS and NIRS imaging is particularly advantageous in identifying the distribution of lipid core plaques and exploring the relationship between vascular geometry, shear stress, and plaque composition [ 52 ]. While IVUS alone can detect fibrous atherosclerotic plaques, which may be obscured by the presence of calcification, NIRS can detect lipids even in the presence of calcifications [ 53 ]. In the PACMANAMI randomized clinical trial, the combination of IVUS and NIRS was successfully utilized to evaluate the effect of statins on plaque burden and composition [ 54 ].…”
Section: Biomarkers Of Invasive Imagingmentioning
confidence: 99%
“…In this context, optical coherence tomography (OCT) emerges as a promising and dynamic imaging-based modality for the real-time visualization of microvascular structures. OCT offers an impressive spatial resolution of around 10 μm in tissue [ 189 ], which is approximately ten times higher than IVUS [ 53 ]. This makes OCT well-suited for investigating plaque microstructure, fibrous cap thickness, and lipid-rich regions, which are crucial indicators of plaque instability [ 41 ].…”
Section: Evaluating Imaging Modalities: a Comparative Approachmentioning
confidence: 99%
“…Placement of an IVUS probe in the vessel allows for better visualization of the vessel dimensions and plaque morphology, thus assisting with interventional treatment. Furthermore, IVUS improves the assessment of plaque characteristics such as shape, size, and location, and enables real-time observation of plaque composition and texture (57). With improvements in technology, IVUS has been further developed with the emergence of a more complete technique, virtual histology-IVUS.…”
Section: Ultrasoundmentioning
confidence: 99%
“…Contrast-enhanced ultrasound is a technique that involves injection of microbubbles during an ultrasonic examination to enhance the reflective signal, allowing accurate assessment of the lumen and neovascularity within carotid plaques (57). Compared to conventional contrast agents, microbubbles eliminate the limitations of radiation exposure and nephrotoxicity (77).…”
Section: Ultrasoundmentioning
confidence: 99%